AN INVESTIGATION OF STUDENTS’ ATTITUDE TOWARD THE USE OF GOOGLE TRANSLATOR IN LEARNING PROCESS OF ENGLISH EDUCATION DEPARTEMENT OF BATURAJA UNIVERSITY - Sintia Septinaria; Henny Yulia; Neti Lastri (Program Studi Pendidikan Bahasa Inggris - Fakultas Keguruan dan Ilmu Pendidikan - Universitas Baturaja, 2022)
The objectives of the study were to investigate the students’ attitude toward the use of googletranslator, the students frequency of using google translator in learning process and problemswhen using GT and solutions. This study was a case study. The population of this study wasall students of English Education Department of Baturaja University. The researchers usedtotal sampling to take the sample , the sample was all the students of English EducationDepartment. The data collected through the questionnaire and interview. The result of thestudy showed that students’ attitude toward the use of google translator in leaning process werein positive category. The students responses on the attitude aspect were on interval 41% -100% that included in positive attitude. The data of the frequency of GT showed that the meanscore was on 2.34 – 3.66 that means on moderate level. In addition, the result of questionnaireasking about the problems of using GT showed that using GT was not always correct, thesolutions that students found were double check the result of GT. The next problem was aboutsignal which make students cannot access GT and the solutions were using their own effort totranslate it such as using dictionary or another resources.